Student-Generated Concept Cartoons as Multimodal Learning Tools for Conceptual Understanding in Primary Science Education: A Case Study from Türkiye - Ethem Gürhan; Makherus Sholeh (Universitas Negeri Semarang, 2026)
Persistent misconceptions in force and motion continue to challenge conceptual understanding in primary science education, particularly within teacher-centered learning contexts that limit students' epistemic agency. Although researchers widely use concept cartoons to stimulate discussion, most studies focus on teacher-generated materials and rarely explore the pedagogical potential of student-generated concept cartoons. This study investigates how student-authored concept cartoons function as multimodal learning tools to promote conceptual change among fourth-grade students. This study employed a mixed-methods case study with an embedded quasi-experimental design in a public primary school in western Türkiye, involving 30 students assigned to an experimental group and a comparison group receiving conventional learning. Quantitative pre- and post-test data were analyzed using inferential statistics and effect size calculations. The study thematically analyzed qualitative data from student-generated artifacts, classroom observations, and interviews using a multimodal representation framework. The findings revealed a statistically significant improvement in the experimental group's conceptual understanding, with a large effect size (Cohen's d = 1.89), alongside marked gains in visual representational accuracy and dialogic reasoning. These results indicate that learning improvements stemmed not merely from visual exposure but from students' active authorship and negotiation of scientific representations. The study concludes that student-generated concept cartoons serve as effective learning and formative assessment tools, supporting student-centered multimodal pedagogy aligned with SDG 4 and current curriculum reform initiatives in Türkiye.